(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
Community education has a long, rich and varied tradition within Scotland. This has often led to debates about its meaning and purpose. In this article I will suggest, through an exploration of the historical context of Scottish community education, that rather than trying to define the meaning of community education, we should value its inherent ambivalence. It is within the spaces of contradiction and contestation that the power structures and politics that struggle to define and shape the field of community education are brought into sharp relief.